Diseño e implementación de un módulo didáctico en automatización industrial aplicando buses de campo para la empresa ECUAINSETEC - Arias Toapanta, Marco Vinicio (2013)
Ecuainsetec Firm has implemented pneumatic and electro-pneumatic training modules to train industrial professionals, as well as demonstrative modules with specific elements from every firm represented by such enterprise in Ecuador so as to increase prestige and show its diverse products. Industrial automation is one of the areas that has not been covered, for which, different industrial elements available within the enterprise have been taken into account in order to create a didactic module with practices focused on true industrial processes, so as to promote initiative from every professional person attending the course, optimize processes and resources in the work area where they daily work. Practices didactic guide sheets follow a pedagogic sequence that allow right teaching on programming languages existent in diverse PLC trademarks, so that the participant can work with any PLC trademark independently from its programming language. The use of industrial equipment in the pneumatic, electro-pneumatic area, industrial sensors and instrumentation included in our module, shall allow the participant adapt to any industrial equipment with the same characteristics, optimizing time for connection and decreasing errors for lack of information. This project describes implementation of a didactic module with the most diverse variables measuring instruments in the industrial field, such as pressure, level, caudal, temperature used as guide to be applied in different industrial processes. Connection and programming for digital or analogical inputs and outputs with different industrial conditions were made. The objective is the participant, with diverse existent programming language, program them in a fast, sure and effective way. Diverse industrial equipment connected to the PLC with Ethernet communication, through the creation of a view interface in Codesys environment, allowed us, through the communication protocol, observing its behavior during the practice development. Intouch environment and HMI screens programming were made by using its diverse programming tools available to simulate a true integrated process with view screen. They connected to our PLC by using an Ethernet field bus, indicating the procedure step by step on practices guide sheets, helping as technical support for the course and the industrial field. Variables and processing data were connected to a slave PLC, which was connected to a master PLC via Profibus to retransmit its data to a computer via Ethernet. A little integrated system for automation was made, using field buses. This new module will achieve increasing sales in the enterprise, and increase reliability for technical trainings offered by it.